PCT162 : Photography composition / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This course will include the fundamental element and principle of composition development of advanced photographic techniques. The course begins with an essential of basic skills designed to teach students to explain the composing of the subject matter towards the current trends and practice. Students learn to follow the skill and techniques with an essential skills and creativity, construct and produce a coherent image and form a good image with a positive value, ethics and professionalism from other photographers with current trends and practices. Student learn to study an issues and explore new techniques, learn to read and critique photograph and follows the developments in digital photography.